The non-linear effects of fixed broadband on economic growth in Africa - Jean C. Kouam; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
The study assesses the non-linear nexus between fixed broadband and economic growth. It focuses on data from 33 African countries for the period 2010 to 2020. The empirical evidence is based on unit root tests, panel smooth transition regression, and the generalized method of moments. The following findings are established: (i) The proportion of the population with access to electricity above and below which the relationship between fixed broadband and economic growth changes in sign is about 60%.(ii) Below this threshold, each 1% increase in fixed broadband subscriptions induces a decline in the economic growth of about 2.58%. Above the threshold, economic growth would increase by 2.43% when fixed broadband subscriptions increased by 1%. Sensitivity analyses and GMM estimation show that these results are robust. Therefore, due to the COVID-19 pandemic, which requires countries to take adequate measures to curb the spread of the pandemic, especially by means of virtual economic activities, any national policy aiming at improving the access of populations to high levels of fixed broadband services should be preceded by the implementation of an electrification program for at least 60% of the total population. Otherwise, providing a good quality internet connection for the benefit of the population would not produce the expected effects on economic growth and would therefore be counterproductive. This study complements the extant literature by providing thresholds at which fixed broadband affects economic growth.
Keywords: E23; F21; F30; L96; O55; 330; Africa; Fixed broadband; Economic growth; Non-linear effects